Long-Term Treatment With Letrozole in a Boy With Familial Male-Limited Precocious Puberty - Yuan, Xin; Chen, Ruimin; Zhang, Ying; Yang, Xiaohong; Lin, Xiangquan (Frontiers in Endocrinology, 2022)
Background The long-term follow-up in children with familial male-limited precocious puberty (FMPP) who were treated with letrozole, triptorelin and spironolactone, is limited, especially considering the efficiency and safety. Objective We describe the clinical characteristics and long-term treatment with letrozole on adult height of a boy diagnosed with FMPP, confirmed by analysis of the LHCGR gene. Methods Physical examinations, bone age (BA), testosterone and gonadotropin levels were measured as well as gene sequencing of the proband and parents. Results The boy was referred to hospital at 3.1yr due to peripheral precocious puberty. His height was 116.8cm (+5.1SD) and BA was 9yr. Genetic analysis revealed a patrilineal c.1703C>T.(p.Ala568Val) mutation of the LHCGR gene. After treating with letrozole for 1.6 years, the height according to BA went from -3.52SD to -2.82SD. Triptorelin was added at age 4.7years based on both the evidence of central puberty and his growth velocity according to BA. During the 6.9 years of treatment, he had a height gain of 51.9cm, and BA increased 5.2 years. At age 10, his present height is 168.7cm (0.05SD) and BA is 14.7yr. No adverse effects of treatment were encountered. Conclusion A patrilineal mutation of the LHCGR gene has been identified in a boy with FMPP. His height is 168.7cm (-0.05SD) which is approaching his adult height after long-term treatment with letrozole, triptorelin and spironolactone.